Prepregnancy Health Care Engagement Among American Indian and Alaska Native People Before and After the Affordable Care Act - Danielle R. Gartner; Katlyn Hettinger; Heather Howard-Bobiwash; Claire E. Margerison (Mary Ann Liebert, 2024)
Background: Despite including several provisions focused on American Indian and Alaska Native (AI/AN) people, few studies look at the Affordable Care Act (ACA)'s potential impact among AI/AN birth givers, a group that experiences a disproportionate burden of adverse pregnancy outcomes. While ACA repeal conversations are ongoing, our objective was to examine changes, and equity in changes, in health care interactions before and after the ACA between AI/AN birth givers and white birth givers. Materials and Methods: We used the 2009?2015 data from the Pregnancy Risk Assessment Monitoring System, a state-level representative sample of individuals with live births. We included those identifying as AI/AN people or white people to estimate change over time in five health measures. We used adjusted linear probability regression models to compare prepregnancy recall periods before, during, and after the implementation of the ACA with the period just before implementation. Results: Among AI/AN birth givers, prepregnancy Medicaid coverage, multivitamin/prenatal use, and teeth cleaning increased by 10 percentage points (ppts), 5 ppts, and 9 ppts, respectively, and were larger than increases experienced by white birth givers (5, 3, and 2?4 ppts, respectively). Increases in preventive health care screening (12?18 ppts) and provider conversation (8?10 ppts) were similar for AI/AN birth givers and white birth givers. Discussion: While some ACA-associated increases in health care coverage and care were quantitatively larger among AI/AN birth givers compared with white birth givers, the existence of pre-ACA disparities suggests that the ACA may have reduced, but may not have eliminated, health inequities between AI/AN birth givers and white birth givers.